Burning of Cotton Fabric Impregnated by Dipotassium Hydrogen Phosphate as a Flame Retardant - MORTEZA MOSTASHARI, SAYED; FALLAH MOAFI, HADI (Asian Journal of Chemistry, 2010)
The effect of dipotassium hydrogen phosphate as a nondurable finish on the flammability of 100 % cotton fabric,woven construction, weighing 160 g/m2 has been of interest in this study. The launched bone-dried, weighed fabrics were impregnated with suitable concentrations of aqueous dipotassium hydrogen phosphate solutions by means of squeeze rolls and dried at 110ºC for 0.5 h. Afterwards, they were cooled in a desiccator, re-weighed with an analytical precision and kept under ordinary conditions before the fulfillment of the vertical flame test. The optimum add-on value to impart flame retardancy expressed in g anhydrous dipotassium hydrogen phosphate per 100 g fabric was about 17.88 %. The results obtained comply with Coating theory and Chemical theory and also Condensed phase retardation.